2007
DOI: 10.1091/mbc.e07-05-0461
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4,5-Bisphosphate Mediates the Targeting of the Exocyst to the Plasma Membrane for Exocytosis in Mammalian Cells

Abstract: The exocyst is an evolutionarily conserved octameric protein complex that tethers post-Golgi secretory vesicles at the plasma membrane for exocytosis. To elucidate the mechanism of vesicle tethering, it is important to understand how the exocyst physically associates with the plasma membrane (PM). In this study, we report that the mammalian exocyst subunit Exo70 associates with the PM through its direct interaction with phosphatidylinositol 4,5-bisphosphate (PI(4,5)P 2 ). Furthermore, we have identified key co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
251
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(258 citation statements)
references
References 46 publications
4
251
0
3
Order By: Relevance
“…It is likely that vesicular trafficking events such as transcytosis redirect membrane protein incorporation to the apical or basolateral membranes in response to a shift in the local ratio of phosphoinositides. As mentioned earlier, in both yeast and mammalian cells, exocyst components Sec3 and Exo70 interact directly with PI(4,5)P 2 , and this interaction is important for vesicle tethering at the plasma membrane during exocytosis (He et al 2007b;Liu et al 2007;Zhang et al 2008). It is therefore likely that secretion machinery such as the exocyst complex is recruited to specific domains of the plasma membrane for exocytosis.…”
Section: Phosphoinositides Regulate Plasma Membrane Asymmetrymentioning
confidence: 84%
See 1 more Smart Citation
“…It is likely that vesicular trafficking events such as transcytosis redirect membrane protein incorporation to the apical or basolateral membranes in response to a shift in the local ratio of phosphoinositides. As mentioned earlier, in both yeast and mammalian cells, exocyst components Sec3 and Exo70 interact directly with PI(4,5)P 2 , and this interaction is important for vesicle tethering at the plasma membrane during exocytosis (He et al 2007b;Liu et al 2007;Zhang et al 2008). It is therefore likely that secretion machinery such as the exocyst complex is recruited to specific domains of the plasma membrane for exocytosis.…”
Section: Phosphoinositides Regulate Plasma Membrane Asymmetrymentioning
confidence: 84%
“…Recently, it was found that the yeast Exo70 (He et al 2007b) and Sec3 ) bind directly to PI(4,5)P 2 on the plasma membrane. This proteinlipid interaction is conserved from yeast to mammals (Liu et al 2007). These interactions play a critical role in recruiting Exo70, Sec3, and ultimately the other exocyst components to the plasma membrane for vesicle tethering (Fig.…”
Section: Membrane Organization and Dynamics In Cell Polaritymentioning
confidence: 99%
“…The GTPase proteins Rho3 and Cdc42 also interact with Exo70 and Sec3 to facilitate the assembly of the exocyst complex at the plasma membrane (He et al, 2007;Moskalenko et al, 2002). In mammalian cells, Exo70 facilitates exocyst association with the plasma membrane through its interaction with TC10 (the orthologue of Cdc42) (Inoue et al, 2003;Liu et al, 2007). In yeast, secretory vesicles acquire the Rab GTPase protein Sec4, which directly interacts with the exocyst, via the Sec15 subunit, thus allowing the secretory vesicle to be recognised by the exocyst plasma membrane complex.…”
Section: The Molecular Machinery For Exocytosismentioning
confidence: 99%
“…Another example is the yeast protein Cla4, which interacts with both PI4P and Cdc42 and requires inputs from both signaling pathways (30). Recently, we found that PI(4,5)P 2 interacts with members of the exocyst complex and is important for polarized exocytosis (13,18,31). In particular, we have found that the exocyst component Sec3, through its N terminus, interacts with and is synergistically regulated by Cdc42 and PI(4,5)P 2 during polarized exocytosis (18).…”
Section: Discussionmentioning
confidence: 99%